Body size of Chrysomelidae (Coleoptera, Insecta) in areas with different levels of conservation in South Brazil - Linzmeier, Adelita M. (Pensoft Publishers, 2011)
Abstract. Body size is correlated with many species traits such as morphology, physiology, life history and abundance as well; it is one of the most discussed topics in macroecological studies. The aim of this paper was to analyze the body size distribution of Chrysomelidae, caught with Malaise traps during two years in four areas with different levels of conservation in the Araucaria Forest, Paraná, Brazil, determining if body size is a good predictor of abundance, and if body size could be used to indicate environmental quality. Body size was considered the total length of the specimen from the anterior region of head to the apex of abdomen/elytron. Measurements were taken for up to ten specimens of each species for each area and for all specimens of those species represented by fewer than ten individuals. The highest abundance and richness of Chrysomelidae were obtained in the lowest body size classes. This herbivorous group showed a trend toward a decrease in body size with increasing abundance, but body size was not a good predictor of its abundance. There was a trend toward a decrease in body size from the less to the most conserved areas; however, the definition of a pattern in successional areas not seems to be entirely clear.